Determinants of the Growth Semi-Elasticity of Poverty Reduction - Mark Misselhorn; Stephan Klasen (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
In this paper we examine the mathematical relationship between growth and distributional change on absolute (i.e. percentage point) changes in FGT poverty measures assuming a log-normal distribution. We also test the empirical relationship of the derived semi-elasticities of growth and distributional change on poverty and find them to explain changes in poverty very well (in fact, better than a related study by Bourguignon (2003) that studied the 'regular' growth elasticity of poverty reduction). This relationship will allow us to predict where growth and distributional change will have the largest (absolute) impact on poverty reduction, which is very useful for predicting and analyzing progress towards meeting MDG1.
Keywords: 330